Hypertrophy Regression With N-Acetylcysteine in Hypertrophic Cardiomyopathy (HALT-HCM): A Randomized, Placebo-Controlled, Double-Blind Pilot Study. Issue 8 (13th April 2018) - Marian, Ali J.; Tan, Yanli; Li, Lili; Chang, Jeffrey; Syrris, Petros; Hessabi, Manouchehr; Rahbar, Mohammad H.; Willerson, James T.; Cheong, Benjamin Y.; Liu, Chia-Ying; Kleiman, Neal S.; Bluemke, David A.; et al.
Abstract : Rationale: : Hypertrophic cardiomyopathy (HCM) is a genetic paradigm of cardiac hypertrophy. Cardiac hypertrophy and interstitial fibrosis are important risk factors for sudden death and morbidity in HCM. Oxidative stress is implicated in the pathogenesis of cardiac hypertrophy and fibrosis. Treatment with antioxidant N-acetylcysteine (NAC) reverses cardiac hypertrophy and fibrosis in animal models of HCM. Objective: : To determine effect sizes of NAC on indices of cardiac hypertrophy and fibrosis in patients with established HCM. Methods and Results: : HALT-HCM (Hypertrophy Regression With N-Acetylcysteine in Hypertrophic Cardiomyopathy) is a double-blind, randomized, sex-matched, placebo-controlled single-center pilot study in patients with HCM. Patients with HCM, who had a left ventricular wall thickness of ≥15 mm, were randomized either to a placebo or to NAC (1:2 ratio, respectively). NAC was titrated ⩽2.4 g per day. Clinical evaluation, blood chemistry, and 6-minute walk test were performed every 3 months, and electrocardiography, echocardiography, and cardiac magnetic resonance imaging, the latter whenever not contraindicated, before and after 12 months of treatment. Eighty-five of 232 screened patients met the eligibility criteria, 42 agreed to participate; 29 were randomized to NAC and 13 to placebo groups. Demographic, echocardiographic, and cardiac magnetic resonance imaging phenotypes at the baseline between the 2 groups were similar. WSE in 38 patients identified a spectrum of 42 pathogenic variants in genes implicated in HCM in 26 participants. Twenty-four patients in the NAC group and 11 in the placebo group completed the study. Six severe adverse events occurred in the NAC group but were considered unrelated to NAC. The effect sizes of NAC on the clinical phenotype, echocardiographic, and cardiac magnetic resonance imaging indices of cardiac hypertrophy, function, and extent of late gadolinium enhancement—a surrogate for fibrosis—were small. Conclusions: : Treatment with NAC for 12 months had small effect sizes on indices of cardiac hypertrophy or fibrosis. The small sample size of the HALT-HCM study hinders from making firm conclusions about efficacy of NAC in HCM. Clinical Trial Registration: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT01537926. Abstract : Supplemental Digital Content is available in the text.